Multi-Owned Property in the Asia-Pacific Region Rights, Restrictions and Responsibilities (Palgrave Macmillan UK, 2018)
This book provides critical insight into the experience of multi-owned property, and showcases different cultural responses across the Asia-Pacific region. Escalating demand for properties within global cities has created exuberance around apartment living; however less well understood are the restrictions on individual rights and responsibilities associated with collective living. In contrast to the highly populated and traditional communal housing arrangements of past Asian economies, we see an increasing focus on neo-liberalist, market-based policies associated with the rise of an Asian middle class shaping structural change from communal to individualistic. This edited collection unpacks the rights, restrictions and responsibilities of multi-owned property ownership across the Asia-Pacific region; examining the experiences of developers, strata-managers, owners and residents. In doing so, they highlight how the rights of one party affects the restrictions and responsibilities of others within different policy frameworks. This work will reach an interdisciplinary audience including scholars and practitioners of sociology, public policy, urban studies and planning, economics, property management and architecture.